Recent Metformin Adherence and the Risk of Hypoglycaemia in the Year Following Intensification with a Sulphonylurea - Min, Jea Young (Diabet Med, 2018)
AIMS: People with unrecognized suboptimal adherence to antihyperglycemic medications may have their regimens intensified, potentially exposing them to high risk of adverse events. We evaluated whether recent low adherence to metformin monotherapy is associated with hypoglycaemia following sulphonylurea addition. METHODS: We assembled a retrospective cohort of veterans who filled a new prescription for metformin from 2001 through 2011 and intensified treatment with a sulphonylurea after ≥1 year of metformin use. We calculated metformin adherence from pharmacy data using the proportion of days covered in the 180-day period before intensification. The primary outcome was hypoglycaemia, defined as a hospitalization or emergency department visit due to hypoglycaemia or an outpatient blood glucose measurement <3.3 mmol/L in the year following intensification. Cox proportional hazards models compared the risk of hypoglycaemia between participants with low (<80%) and high (≥80%) adherence. Adherence was also modelled as a continuous variable using restricted cubic splines. RESULTS: Of 187,267 participants who initiated metformin monotherapy, 49,424 added a sulphonylurea after ≥1 year. The median adherence was 87% (IQR 50, 100), and 43% had adherence <80%. Hypoglycaemia rates were 23.1 (95% confidence interval [CI] 21.1,25.4) and 24.5 (95% CI 22.7,26.4) per 1000 person-years among low and high adherence participants, respectively (adjusted hazard ratio 0.95, 95% CI 0.84,1.08). The risk of hypoglycaemia was similar across all levels of adherence when adherence was modelled as a continuous variable. CONCLUSIONS: We found no evidence that past low adherence to metformin monotherapy was associated with hypoglycaemia following intensification with a sulphonylurea.